2018
DOI: 10.1089/trgh.2017.0045
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Neovaginal Candidiasis in Transgender Women After Penile Inversion Vaginoplasty: A Clinical Case Series of Five Consecutive Patients

Abstract: Background: Vaginoplasty is performed as gender-affirming surgery in transgender women. While multiple surgical techniques exist for this goal, penile inversion vaginoplasty is performed most frequently. Neovaginal symptoms may impede sexual functioning after surgery.Methods: A total of five consecutive patients with symptoms and positive swabs for neovaginal candida infection were described.Results: All patients presented with white-colored neovaginal discharge and some with neovaginal itching and/or malodor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…One study found that the neovaginal microbiome was highly diverse, composed largely of anaerobic bacteria, and triggered a host response similar to the response to BV 59 . Another study examining the neovaginal microbiome of five women with candida infection following neovaginal surgery found these women also had more BVAB in their vaginal microbiome 60 . Importantly, all five women in this study experienced several negative vaginal symptoms that were attributed to the microbiome and not just candida infection.…”
Section: Gender Affirming Treatmentmentioning
confidence: 98%
“…One study found that the neovaginal microbiome was highly diverse, composed largely of anaerobic bacteria, and triggered a host response similar to the response to BV 59 . Another study examining the neovaginal microbiome of five women with candida infection following neovaginal surgery found these women also had more BVAB in their vaginal microbiome 60 . Importantly, all five women in this study experienced several negative vaginal symptoms that were attributed to the microbiome and not just candida infection.…”
Section: Gender Affirming Treatmentmentioning
confidence: 98%
“…Until recently, data on the microbiota colonizing the neovagina were limited to case reports and small studies that used limited culture-based detection methods or targeted PCR to detect the presence of specific species of interest (classic STI pathogens or Lactobacillus spp.) (Bodsworth et al, 1994;Haustein, 1995;Weyers et al, 2009;Weyers et al, 2010;de Haseth et al, 2018;Radix et al, 2019). These assays fail to capture the vast majority of species present and provide no information on the composition or structure of bacterial communities in the neovagina.…”
Section: The Neovaginal Microbiomementioning
confidence: 99%
“…Neovaginal swabs sent for clinical diagnostics frequently return the results "altered vaginal flora inconsistent with bacterial vaginosis" and treatments established for the EDV (metronidazole) are frequently ineffective (Jain and Bradbeer, 2007;van der Sluis et al, 2020). Candidiasis is another common cause of vaginal itching in the EDV; there has been one case series published reporting neovaginal candidiasis in five individuals (de Haseth et al, 2018), warranting further characterization of neovaginal candida species and the development of clinical guidelines for prevention and treatment. The cause of neovaginal malodour also warrants further investigation.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…Vaginal flora is primarily bacteria typically found on the skin and occasionally lactobacilli. Bacterial vaginosis is unlikely, and Candida is rare . If an infection is noted, take aerobic and anaerobic bacterial cultures and recommend that the client douche for a few days to a week.…”
Section: Transfeminine Preventive Carementioning
confidence: 99%